2015
DOI: 10.1007/s11743-015-1701-y
|View full text |Cite
|
Sign up to set email alerts
|

Shape of Long Chain Alkyl Sulfonate Micelle upon Salt Addition: a Molecular Dynamics Study

Abstract: Here we report a molecular dynamics simulation on the state of long chain alkyl sulfonate micelle which occurs in the presence of salt. We tracked the formation of a large micelle with a dumbbell-like shape, which has hemispherical end caps with a large radius rather than the middle cylindrical body, where the shape bending angle was around 160 o . The data from chain analysis indicate that the micelle hydrocarbon layer is covered with disordered tails. We also report micelle fission controlled by changes in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 22 publications
2
2
0
Order By: Relevance
“…Cylindrical micelles present as semiflexible rods with spherical end-caps that are larger in diameter than the main cylinder body. This dumbbell shape for rod micelles has been predicted by theory and observed in molecular dynamics simulations . In this work, we also observe the formation of these dumbbell-type structures at concentrations around and above the sphere-to-rod transition (see the structures in Figure a).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Cylindrical micelles present as semiflexible rods with spherical end-caps that are larger in diameter than the main cylinder body. This dumbbell shape for rod micelles has been predicted by theory and observed in molecular dynamics simulations . In this work, we also observe the formation of these dumbbell-type structures at concentrations around and above the sphere-to-rod transition (see the structures in Figure a).…”
Section: Resultssupporting
confidence: 85%
“…This dumbbell shape for rod micelles has been predicted by theory 75 and observed in molecular dynamics simulations. 76 In this work, we also observe the formation of these dumbbell-type structures at concentrations around and above the sphere-torod transition (see the structures in Figure 5a).…”
Section: Journal Of Chemical Theory and Computationsupporting
confidence: 61%
“…Systematic research effort over the years has resulted in a considerable amount of computational work on model SDS aqueous solutions employing either coarse-grained (CG) or united-atom (UA) or even all-atom (AA) force fields. For example, using the MARTINI Force Field (FF) ,, or other CG models, good estimates of the first CMC , and of the mean aggregation number of micelles have been obtained for certain SDS concentrations. , Dissipative particle dynamics (DPD) simulations have also offered a qualitative description of the morphological properties of aqueous SDS solutions.…”
Section: Introductionmentioning
confidence: 99%
“…9 The effect of the interaction parameters between the surfactant and the counter-ion over micelle structure, which to some extent presents similar effects of possible counterions exchanges, was studied by de Moura and Freitas 10 and by Tang et al 11 The salt concentration was also showed to have significant effects over the shape and dynamics of aggregates in self-assembled systems. 12,13,14,15 Here, we will compare the widely used surfactant sodium dodecyl-sulfate (SDS) with the choline dodecyl-sulfate (ChDS). The micelles formed by dodecyl-sulfate are well-behaved and stable.…”
Section: Introductionmentioning
confidence: 99%